Branding Space: Deliberate Formations in Beginning Design - McManus Margaret (SHS Web of Conferences, 2019)
Arguably, ambiance in our culture is created in large by architecture and media. The former consumes us as we inhabit spaces both interior and exterior, allowing physical and material constraints — and the programmatic functions they permit — to create ambiance. The latter, media, inhabits us as we consume it. It creates or perhaps manipulates an ambiance within our minds. Through signage, television, and the internet we have graphic design flooding our brains via advertising and marketing: emotionally directing our decisions, telling us to buy this or invest in that. Analogous to material and physical choices that create the ambiance of architecture, we can blame branding strategies and the practices thereof for the strength and power that they give media to create ambiance. While students use branding strategies to assist themselves in creating ambiance through architecture, they are becoming grounded in a process that compels them to carry out objectives and promises made. Ultimately, this undertone of the pedagogical approach is what they can take forward as they embark on more complex projects, where timely decisions must coincide with a singular message and clear vision.